Commercial Republicanism in the Dutch Golden Age The Political Thought of Johan & Pieter de la Court - Weststeijn, Arthur (Studies in the History of Political Thought, 2012)
The Dutch seventeenth century, a 'Golden Age' ridden by intense ideological conflict, pioneered global trade, participatory politics and religious toleration. Its history is epitomized by the life and works of the brothers Johan (1622-1660) and Pieter de la Court (1618-1685), two successful textile entrepreneurs and radical republican theorists during the apex of Dutch primacy in world trade. This book explores the many facets of the brothers' political thought, focusing on their ground-breaking argument that commerce forms the mainstay of republican politics. With a contextual analysis that highlights the interaction between thinking and acting, between intellectual and cultural history, the book reveals the international significance of this commercial republicanism and it proposes a novel, rhetorical approach to seventeenth-century Dutch political culture.